Crianças que sofrem: representações da infância em livros distribuídos pelo PNBE - Rosa Maria Hessel Silveira (Universidade de Brasília, 2015)
This article analyzes representations of childhood/child in Brazilian contemporary children's literature from the theoretical and methodological framework of cultural studies in education. As a part of a larger study that has sought to understand the factors involved in receiving books that make up the collections of the National Program Library in School (PNBE) – Early Years of Elementary School, this text discusses the representations of children suffering and the different origins of suffering according to three main themes: poverty and child l abor, difficulties in social interaction and children's fears. The analysis is based on eight books by Brazilian authors that are part of the 2012 and 2014 collections of PNBE, and which contains verbal narratives with illustrations and wordless books.